The "Demise of the Caregiving Daughter"? Gender Employment Gaps and the Use of Formal and Informal Care in Europe - Eric Bonsang; Joan Costa-Font (Institute of Labor Economics (IZA), 2023)
We revisit the universality of the "caregiving daughter effect", which holds that daughters tend to provide more care to their older parents than sons. Based on rich European data, we document evidence of such an effect in countries with large gender disparities in employment rates, where having daughters also depresses the demand for formal care. In contrast, we find evidence consistent with the "demise of the caregiving daughter" when exposed to narrower gender gaps, where there is no more daughters' effect on formal care. These results point to a reconsideration of caregiving system design amidst the rise of female employment.
Keywords: I18; J14; J3; 330; informal care; formal care; daughters; caregiving daughter effect; gender employment gap; Europe; care substitution; social norms